Disapproval of the provisional agreements and the advance termination in the preparatory investigation stage in the Huánuco Fiscal District, 2016-2017 - Silva-Carhuaricra, Mylene K. (2019)
The objective of this work was to identify the factors that influence the disapproval of the provisional agreements of early termination, in the preparatory investigation stage in the Fiscal District of Huánuco, 2016 - 2017. The study method for its purpose is basic, because , had as its purpose the best understanding of the phenomena, to generate new knowledge and new theories, by the main function that will meet the de- scriptive level, since its purpose was to perform an analysis of the current state of the phenomenon, deter- mining its characteristics and properties; and explanatory, because it was oriented to discover and predict in a rigorous way the legal problematic related to the disapproval of the provisional agreements and the early termination by the corporate provincial prosecutors, in the cases subject to research in the city of Huánuco, the population-sample under study, was made up of 72 Provincial Criminal Prosecutors Corporations of the Fiscal District of Huánuco. The results of the 1008 data obtained 69.94% (705) positively affirm that it is the sincere confession of the accused, disapproval of the provisional agreements and early termination, which determine the preparatory investigation in the Fiscal District of Huánuco. While 28.87% (291) of the agree- ments deny this possibility. On the other hand, 1.19% (12) consider that this happens only sometimes. It is concluded that, the factors that influence the disapproval of the provisional agreements of early termination in the preparatory investigation stage, we have: the application of the judicial determination of the pun- ishment, the motivation of the provisional agreements and the use of the consensual institution.